ITGB4 deficiency induces DNA damage by downregulating HDAC1 in airway epithelial cells under stress stimulation. Issue 10 (21st October 2022) - Xu, Kun; Yao, Ye; Liu, Huijun; Yang, Ming; Yuan, Lin; Du, Xizi; Yang, Yu; Qin, Ling; Wang, Weijie; Zhou, Kai; Wu, Xinyu; Liu, Chi
Abstract: Background: DNA damage in airway epithelia under exogenous disruptors can trigger various pulmonary diseases. Integrin beta 4 (ITGB4) is a structural adhesion molecule, which is indicated to regulate the process of DNA damage in airway epithelia for its unique long cytoplasmic domain subunit. Methods: The expression level of ITGB4 and the degree of DNA damage were observed in the house dust mite (HDM)‐stressed model and ozone‐challenged model, respectively. Besides, ITGB4 conditional knockout mice and ITGB4‐deficient airway epithelial cells were constructed to observe the influence of ITGB4 deficiency on DNA damage. Furthermore, the influence of ITGB4 deficiency on HDAC1 expression in airway epithelia was determined under stress stimulation. Finally, corresponding intervention strategies were carried out to verify the involvement of the ITGB4‐mediated HDAC1 pathway in DNA damage of airway epithelial cells. Results: HDM stress and ozone challenge reduced the expression of ITGB4, which is accompanied by the increased expression of 8‐oxoG and γ‐H2AX both in vivo and in vitro. Moreover, ITGB4 deficiency in airway epithelia aggravates the degree of DNA damage under HDM stimulation and ozone stress, respectively. Furthermore, ITGB4 deficiency downregulated the expression of HDAC1 during DNA damage, and restoring HDAC1 can reverse the enhanced DNA damage in airway epithelial cells after exogenous stress. Conclusions: This study confirmed the involvement of ITGB4 in the regulation of DNA damage through mediating HDAC1 in airway epithelial cells under exogenous stress. These results supply some useful insights into the mechanism of DNA damage in airway epithelial cells, which would provide possible targets for early prediction and intervention of pulmonary diseases.